I can help you with this.

You can solve this problem by using the quadratic formula, but since you need to do it by completing the square I'll show you how to do it that way.

x^2 + 5x -11 = 0

a= x^2,b= 5x, andc= -11

1)add c to the other side

x^2 + 5x = 11

2)multiply b by 1/2 and then take the square root

[5(1/2)] = (5/2)^2 = 25/4 = b

3)add b to both sides

x^2 + 5x + 25/4 = 11 + 25/4

4)factor the left side and add the right side

(x + 5/2)^2 = 69/4

5)take the square root of both sides and simplify

x + 5/2 = +/-sqrt(69/4)

x + 5/2 = +/- sqrt(69)/2

6)subtract 5/2 on both sides

x = -5/2 +/- sqrt(69)/2

x = (-5 +/- sqrt(69))/2